Neurodidactics in the training of professionals in early childhood education: Systematic review - Salazar Arango, Edwar (2025)
This systematic review article explores the integration of neuroscientific principles into teacher training. It argues that neurodidactics is crucial for improving teaching and learning by enabling educators to adapt their strategies to students' cognitive and emotional characteristics. However, significant challenges in its implementation are identified, such as resistance to change and a lack of ongoing training in Latin America. The study uses the PICO method to structure the research and the PRISMA method to establish inclusion and exclusion criteria, addressing key questions about the effectiveness of neurodidactic strategies in pre-service teacher training. The review of academic articles reveals a paucity of research in the region, underscoring the need to promote studies that evaluate these practices. The article concludes that neurodidactics should not only be theoretical but also applied in specific educational contexts, promoting meaningful learning and contributing to the improvement of pre-service education by developing specific, professional competencies for future pre-service teachers.